2018
DOI: 10.1167/iovs.17-22377
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Control in the Argus II Retinal-Prosthesis Enables Reduced Head Movement and Better Localization Precision

Abstract: Integrating an eye tracker into the Argus II is feasible, reduces head movements in a seated localization task, and improves pointing precision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…This is a binocular eye-tracking setup using one camera and six glints per eye for gaze tracking. Although the SMI system is no longer available for sale, we chose to include it because a significant number of these head-worn eye-tracking setups have been sold and they are still commonly used in mobile eye-tracking studies (e.g., Ahlstrom, Kircher, Thorslund, & Adell, 2016;Guyader, Ottosson, & Witell, 2017;Caspi et al 2018;Hoppe et al 2018). The glasses were connected to this laptop via a USB cable, and the SMI iViewETG software (version 2.7.1) was used for a three-point calibration and recording.…”
Section: Apparatusmentioning
confidence: 99%
“…This is a binocular eye-tracking setup using one camera and six glints per eye for gaze tracking. Although the SMI system is no longer available for sale, we chose to include it because a significant number of these head-worn eye-tracking setups have been sold and they are still commonly used in mobile eye-tracking studies (e.g., Ahlstrom, Kircher, Thorslund, & Adell, 2016;Guyader, Ottosson, & Witell, 2017;Caspi et al 2018;Hoppe et al 2018). The glasses were connected to this laptop via a USB cable, and the SMI iViewETG software (version 2.7.1) was used for a three-point calibration and recording.…”
Section: Apparatusmentioning
confidence: 99%
“…Caspi et al recently showed that an eye tracker can be used to enable combined eye-head scanning in the Argus II retinal prosthesis users. 14 Other assistive devices may be used in conjunction with the Argus II to provide additional synergistic effects. 15 …”
Section: Patient Selectionmentioning
confidence: 99%
“…Moreover, the thermal sensor can be used with an eye tracker to enable users to scan using combined eye-head movements. 8 Twitter Yingchen He @YingchenHePhD…”
Section: Discussionmentioning
confidence: 99%